PENGARUH BERBAGAI FORMULASI HERBISIDA BERBAHAN BAKU AIR KELAPA FERMENTASI, ASAM ASETAT, ETANOL, GLIFOSAT DAN GARAM TERHADAP GULMA DI LAHAN TERBUKA - Agustina, Beta; Anwar, Risvan; Suzanna, Eka; Kesumawati, Neti (University of Prof. Dr. Hazairin, SH, 2025)
This study aimed to evaluate the effectiveness of various herbicide formulations based on fermented coconut water, acetic acid, ethanol, glyphosate, and salt against weeds in open fields. The study used a Randomized Block Design with 9 formulations and 3 replications. Observed variables included dominant weeds, dead weed area, live weed population, dry weight of live weeds, and chlorophyll degradation. The results showed that four types of weeds dominated the field (96%): Paspalum conjugatum, Mimosa pudica, Cyperus rotundus, and Chrysopogon aciculatus. Herbicide formulations significantly suppressed weed growth. Formulations 3 and 9 proved to be the most effective. Further development of Formulations 1, 3, 4, 5, 7, and 8 is recommended.